Research Landscape On Watershed Management In Indonesia; A Bibliometric Analysis - Muh. Sofyan Budiarto; Ida Widianingsih; R. Ahmad Buchari; Entang Adhy Muhtar; Herri Saksono (Universitas Padjadjaran, 2022)
The research goal is to investigate the evolution of watershed management research through an investigative scientific article published by Indonesian researchers in various journals and conferences indexed by Scopus. Scopus publication data was searched using the terms “watershed management